Potensi Aplikasi Bambu Sebagai Bahan Peredam kebisingan Operasional Kereta Api dengan Menggunakan Model Kristal Sonik Persegi - Handayani, Dewi; Hartono, Widi; Nuha Fadhilah, Sarah (Universitas Veteran Bangun Nusantara, 2024)
Noise is the unwanted sound of a business or activity at a certain level and time that can cause disturbances to human health and environmental comfort. One of the transportation activities that can cause high noise is train. The effort to reduce the noise caused by the train is to build a noise-absorbing building in the form of sonic crystals. This research aims to analyze the potential application of bamboo with a square sonic crystal model as a noise reducer for railway activities. This research method is an experimental method using the method of Ministry of Environment No. 48 of 1996. The noise absorber is made of bamboo-based material arranged with a three-layer square lattice type, a diameter of 8.7 cm ± 0.2 cm, and a height of 2 meters. From the results of this study, it was found that the day and night equivalent noise level (LSM) using the barrier was 90.70 dB, 91.20 dB, 92.09 dB at a distance of 1, 2, and 3 meters. The potential of square lattice bamboo-based sonic crystals as a building damper can reduce the noise level by 8.87 dB (8.91%). Bamboo with this square lattice can be an alternative noise dampening building in the residential area around the railroad.